2017
DOI: 10.15537/smj.2017.4.17855
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Crohn’s disease activity by Doppler sonography

Abstract: Objectives:To investigate the diagnostic accuracy of ultrasound for evaluation of inflammatory activity in patients with Crohn’s disease (CD).Methods:Fifty-six patients with histologically proven CD (39 with active, 17 with inactive disease) and 30 healthy volunteers as a control group were enrolled in the study at WeiFang People’s Hospital, Weifang Province, China from October 2012 to December 2014. Bowel wall thickness, and vascularity pattern were measured by Doppler ultrasound.Results:There was a significa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
2
1
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 29 publications
(32 reference statements)
1
2
1
1
Order By: Relevance
“…Therefore, the thickness of the intestinal wall together with the vascular pattern may be useful for detecting the endoscopic activity of the disease [ 34 ]. Other studies that assessed the superior mesenteric artery flow as a semi-quantitative parameter confirmed the previous observations regarding the correlation between the severity of the disease and Doppler parameters [ 35 , 36 ].…”
Section: Resultssupporting
confidence: 82%
“…Therefore, the thickness of the intestinal wall together with the vascular pattern may be useful for detecting the endoscopic activity of the disease [ 34 ]. Other studies that assessed the superior mesenteric artery flow as a semi-quantitative parameter confirmed the previous observations regarding the correlation between the severity of the disease and Doppler parameters [ 35 , 36 ].…”
Section: Resultssupporting
confidence: 82%
“…The data of our study showed that the difference of BWT between active and inactive group was statistically significant. In this study, the median BWT in active and inactive group was 8.04 ± 3.32 mm and 6.75 ± 2.51 mm, respectively, larger than that was previously reported [27][28][29] . This could be associated with a longer course of the disease in our www.nature.com/scientificreports/ study (average course of disease was about 45 months), and pathological examination showed that severe inflammation accounted for 37.2% in our cases.…”
Section: Discussioncontrasting
confidence: 70%
“…Other changes encountered by the intestine due to inflammation in CD that might affect the PK of oral drugs are reported. These include dilation of the blood vessels [ 78 , 89 ], change of the intestine vascularity [ 90 92 ], change of intestine blood perfusion [ 90 94 ], increase in the thickness of the intestine wall (active CD > 4 mm) [ 78 , 80 , 81 , 83 , 89 , 93 ], submucosal fibrosis and muscularisation [ 91 ] and wrapping of the intestinal wall in fat wrap [ 95 ], but they are beyond the focus of this analysis.…”
Section: Resultsmentioning
confidence: 99%
“…Although an increase of gut wall thickness can affect gut fluid dynamics, a meta-analysis was not carried out for this parameter even though it showed an approximately twofold increase in active CD patients compared to healthy volunteers in the few studies encountered [ 78 , 80 , 81 , 93 , 158 ]. This is because the utility of the intestine loop morphology is not clear in the Simcyp ® M-ADAM model; instead, the villous morphology is established in Simcyp ® .…”
Section: Discussionmentioning
confidence: 99%